2009
DOI: 10.1080/13854040902855358
|View full text |Cite
|
Sign up to set email alerts
|

Reliability Concerns in the Repeated Computerized Assessment of Attention in Children

Abstract: Assessment of attentional processes via computerized assessment is frequently used to quantify intra-individual cognitive improvement or decline in response to treatment. However, assessment of intra-individual change is highly dependent on sufficient test reliability. We examined the test–retest reliability of selected variables from one popular computerized continuous performance test (CPT)—i.e., the Conners’ CPT – Second Edition (CPT-II). Participants were 39 healthy children (20 girls) ages 6–18 without in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…This is in line with previous studies that showed that response time variability in children and adolescents was of modest stability [81] and that response inhibition is stable in test–retest [85]. The present study shows that baseline response speed and working memory were only coincidentally associated with affective problems in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…This is in line with previous studies that showed that response time variability in children and adolescents was of modest stability [81] and that response inhibition is stable in test–retest [85]. The present study shows that baseline response speed and working memory were only coincidentally associated with affective problems in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Taking into account past research on extensive reaction time variability in children (Zabel, von Thomsen, Cole, Martin, & Mahone, 2009), this finding was unexpected, but suggests that measures that are quite simple in their demands, such as reaction time, may allow for the consistent measurement of cognitive outcome in ID syndromes.…”
Section: Discussionmentioning
confidence: 83%
“…Reliability studies of continuous performance tasks typically involve Conners' version of the task, which is widely used in the assessment of ADHD (Conners, 2004). These tasks show high test-retest reliability (>0.85) of commission errors in child and adult samples over short time intervals, from 1 to 2 weeks (e.g., Halperin, Sharma, Greenblatt, and Schwartz, 1991;Soreni, Crosbie, Ickowicz, and Schachar, 2009), and modest reliabilities (0.62 to 0.82) over longer intervals from 3 to 8 months (e.g., Kaminski, Groff, and Glutting, 2009;Zabel et al, 2009). Other more complex versions, such as the immediate and delayed memory task, typically used in adults, also demonstrate high test-retest reliability across consecutive testing days .…”
Section: Task Reliabilitymentioning
confidence: 99%